Pelatihan Literasi Digital Pada Sekolahrumah Salihah Yogyakarta: Animasi, Poster Digital, Video Dan Gim - Nur W. Rahayu; Nanum Sofia (Journal of Appropriate Technology for Community Services, 2021)
Young people could learn and use technology in formal, informal and nonformal education effortlessly. As a legal nonformal education, homeschooling programs become more popular because the programs demonstrate some advantages, such as customized learning materials, personalized learning methods, and flexible learning schedules. However, some homeschooling communities face several problems related to digital literacy skill because of lack of teachers’ capacity and tools. To support digital literacy, a series of training has been conducted for teachers and students at Salihah Homeschool, Yogyakarta. It consisted of training of modern computer technology for teachers and multimedia training for students and parents. The second training taught students on how to make digital posters, videos, animations, and games related to Covid-19 pandemic. Survey showed half of the students were happy with the training activities. Furthermore, the most preferred lessons were animation and digital posters, while game and video tutorials were perceived difficult. Nevertheless, student participation showed a declining trend since the second day of training. Moreover, some parents expressed happiness with the training contents, but there were also parents who found difficulty as the parents were novice users. It implies future efforts to promote positive awareness of the ease of using IT and continuous monitoring to improve digital literacy.